THE INCIDENCE OF PRIMARY ONCOPATHOLOGY OF THE REPRODUCTIVE SYSTEM IN WOMEN OF THE CITY OF KEMEROVO - Елгина, Светлана Ивановна; Анискина, Елизавета Андреевна; Золоторевская, Ольга Сергеевна (Medicine in Kuzbass, 2021)
Objective – to identify the incidence of primary oncopathology of the female reproductive system. Materials and methods. The information was found in medical case histories of 74 women with oncopathology of the reproductive system who were registered at the Women’s Consultation Centre of the Kemerovo State Hospital N 4 within 2017-2020. The average age of the patients was 53.5 years. Results. Breast cancer detected in 43 (58.2 %) women has a leading position, cervical cancer – in 12 (16.3 %) ranks second, the third one is ovarian cancer – in 5 (6.7 %), uterine corpus cancer – in 3 (4.0 %) ison the fourth position, next is vulvar cancer – 2 (2.7 %) and fallopian tube cancer – 1 (1.3 %). Primary oncopathology was detected in 38 (51.3 %) women at stage I (Ia, Ib), in 22 (29.7 %) women – at stage II (IIa, IIb), in 8 (10.8 %) women – at stage III, in 6 (8.1 %) women – at stage IV. It should be noted that the majority of the patients did not seek for medical help from an obstetrician-gynecologist and were not followed up during 5 years or longer – 56 (75.6 %). The screening for reproductive system oncopathology included: cytological screening of 77.0 % (57) women, pelvic ultrasound – 86.4 % (64) women, breast ultrasound – 70.2 % (52) women, mammography – 55.4 % (41) women. Conclusion. Timely screening for oncopathology of the female reproductive system will undoubtedly make the diagnosis of these diseases at an early stage possible, improve the prognosis and decrease mortality.